2006
DOI: 10.1111/j.0105-1873.2006.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

White petrolatum (Ph. Eur.) is virtually non‐sensitizing. Analysis of IVDK data on 80 000 patients tested between 1992 and 2004 and short discussion of identification and designation of allergens

Abstract: True allergic patch test reactions to white petrolatum are extremely rare and probably due to an individually increased susceptibility to allergens and/or irritants. This is in agreement with considering petrolatum as a non-sensitizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…In humans, patch-test studies with medicinal white oils or waxes showed no skin sensitization (in almost 80 000 patients 18 ) or only mild erythema in sporadic cases even on damaged skin. 8,[18][19][20] These cases were never related to cosmetic allergy. White petrolatum and waxes are hence considered non-sensitizers and rarely allergen, the sensitizing components being probably PAH.…”
Section: Cutaneous Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…In humans, patch-test studies with medicinal white oils or waxes showed no skin sensitization (in almost 80 000 patients 18 ) or only mild erythema in sporadic cases even on damaged skin. 8,[18][19][20] These cases were never related to cosmetic allergy. White petrolatum and waxes are hence considered non-sensitizers and rarely allergen, the sensitizing components being probably PAH.…”
Section: Cutaneous Exposurementioning
confidence: 99%
“…In humans, patch‐test studies with medicinal white oils or waxes showed no skin sensitization (in almost 80 000 patients) or only mild erythema in sporadic cases even on damaged skin . These cases were never related to cosmetic allergy.…”
Section: Toxicity and Cutaneous Side‐effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraffinöl in zahlreichen tierexperimentellen Untersuchungen als Vehikel, auch für intradermale Applikationen, verwendet wurde, ohne dabei zu einer Sensibilisierung zu führen, ist eine Sensibilisierung durch den Kontakt nicht zu erwarten. Die kontaktsensibilisierende Wirkung derartiger gereinigter Paraffinöle ist genauso zu bewerten wie die der ebenfalls nicht sensibilisierenden und daher auch im Epikutantest beim Menschen als Vehikel eingesetzten (weißen) Vaseline (Schnuch et al 2006). …”
Section: Hautsensibilisierende Wirkungunclassified
“…Petrolatum rarely causes hypersensitivity reactions, although a few sporadic cases of contact allergy to petrolatum, which is used as a vehicle in patch test preparations, have been reported in humans (Dooms-Goossens and Degreef, 1980;Kang et al, 2004;Kundu et al, 2004;Tam and Elston, 2006). A large retrospective analysis of patch test data in humans indicating true allergic patch test reactions to white petrolatum are extremely rare and probably as a result of an individually increased susceptibility to allergens and/or irritants (Schnuch et al, 2006).…”
Section: Introductionmentioning
confidence: 99%